Cloud empires : how digital platforms are overtaking the state and how we can regain control - Lehdonvirta, Vili (Cambridge, Massachusetts ; London, England : The MIT Press, 2022)
"Companies like Amazon, Upwork, Apple's App Store, and Ebay are shaping the world and the prospects of millions of people who depend on them for their livelihoods. This book explores the implications of this power and shows how it compares with traditional statecraft"-- "Companies like Amazon, Upwork, Apple's App Store, and Ebay are shaping the world and the prospects of millions of people who depend on them for their livelihoods. This book explores the implications of this power and shows how it compares with traditional statecraft"--